Paramagnetic NMR investigation of dendrimer-based host-guest interactions. - Fei Wang (PLoS ONE, 2013)
In this study, the host-guest behavior of poly(amidoamine) (PAMAM) dendrimers bearing amine, hydroxyl, or carboxylate surface functionalities were investigated by paramagnetic NMR studies. 2,2,6,6-Tetramethylpiperidinyloxy (TEMPO) derivatives were used as paramagnetic guest molecules. The results showed that TEMPO-COOH significantly broaden the ¹H NMR peaks of amine- and hydroxyl-terminated PAMAM dendrimers. In comparison, no paramagnetic relaxation enhancement (PRE) was observed between TEMPO-NH₂, TEMPO-OH and the three types of PAMAM dendrimers. The PRE phenomenon observed is correlated with the encapsulation of TEMPO-COOH within dendrimer pockets. Protonation of the tertiary amine groups within PAMAM dendrimers plays an important role during this process. Interestingly, the absence of TEMPO-COOH encapsulation within carboxylate-terminated PAMAM dendrimer is observed due to the repulsion of TEMPO-COO- anion and anionic dendrimer surface. The combination of paramagnetic probes and ¹H NMR linewidth analysis can be used as a powerful tool in the analysis of dendrimer-based host-guest systems.